The Development of Learning Devices Based on Guided Inquiry and Affectivities for Students' Critical Thinking Skills - Lita Sumiyarti; Dadi Setiadi; Jamaluddin Jamaluddin (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: The purpose of this research is to make the learning device based on guided inquiry in science learning and affectivities to improve students’ critical thinking skills and to examine its validity, effectiveness, and practicability. This research adapts Borg & Gall Research and Development and modification. The instruments of the research were instrument validation results, practicality, and effectiveness. Data were collected by employing a validation sheet that was validated by the assessor to gain validation and practicality scores, the student's positive response questionnaire and learning result test sheet were full filled-in by the students, and the observation sheet was full filled-in by the observer. The average score of total validity is in the score range of 2.6<SV≤3.5 and is an invalid category. The result of practicality research of learning devices based on practicality questionnaire the range of 3.5-4.0 and is in a very practice category. The result of effectiveness based on learning result test showed that 75 % of the students are completely based on the results of the research, it can be concluded that the learning device based on guided inquiry is valid, practical, and effective that is feasible to be used in a learning activity in the classroom.Keywords: Development Research; Guided Inquiry; Critical Thinking Skill